The incidence of public sector hospitalisations due to dog bites in Australia 2001–2013. (16th July 2017) - Rajshekar, Mithun; Blizzard, Leigh; Julian, Roberta; Williams, Anne‐Marie; Tennant, Marc; Forrest, Alex; Walsh, Laurence J.; Wilson, Gary
Abstract: Objective : To estimate the incidence of dog bite‐related injuries requiring public sector hospitalisation in Australia during the period 2001–13. Methods : Summary data on public sector hospitalisations due to dog bite‐related injuries with an ICD 10‐AM W54.0 coding were sourced from the Australian Institute of Health and Welfare for the study period 2001–2013. Results : In Australia, on average, 2, 061 persons were hospitalised each year for treatment for dog bite injuries at an annual rate of 12.39 (95%CI 12.25–12.53) per 100, 000 during 2001–13. The highest annual rates of 25.95 (95%CI 25.16–26.72) and 18.42 (95%CI 17.75–19.07) per 100, 000 were for age groups 0–4 and 5–9 years respectively. Rates of recorded events increased over the study period and reached 16.15 (95%CI 15.78–16.52) per 100, 000 during 2011–13. Conclusion : Dog bites are a largely unrecognised and growing public health problem in Australia. Implications for public health : There is an increasing public sector burden of hospitalisations for injuries from dog bites in Australia.